Slow-Speed Resistance Training Increases Skeletal Muscle Contractile Properties and Power Production Capacity in Elite Futsal Players - Iodice, Pierpaolo; Trecroci, Athos; Dian, Dario; Proietti, Giorgia; Alberti, Giampietro; Formenti, Damiano (Frontiers in Sports and Active Living, 2020)
The purpose of this study was to explore the effects of slow-speed resistance training with low intensity (SRT) on muscle power output in elite futsal players with respect to traditional resistance training. The authors hypothesized that the muscle deoxygenation during SRT causes early recruitment of fast twitch fibers that would positively affect strength and power performance. Thirty male elite futsal players were recruited and randomly assigned either to SRT group or to traditional resistance training (TRT) group. All players underwent an 8-weeks experimental protocol consisting of 2 training sessions per week at both leg curl and leg extension machines. In the SRT, players lifted 50% of one maximum repetition (1RM) involving 3 s for eccentric and concentric actions. In the TRT, players lifted 80% of 1RM involving 1 s for eccentric and concentric actions. All players were tested twice (pre and post) for sprint and jump performances, maximal isometric voluntary contraction (MVC) and maximal isokinetic peak torque (Peak TQ) and total work (TW) at 60 and 120°/s (on knee extensors and flexors). The two groups presented remarkable differences in the within-group changes for all the variables. SRT exhibited greater improvements in both Peak TQ and TW for knee extensors and flexors at 120°/s. Conversely, TRT showed greater improvements in MVC, and in both Peak TQ and TW for knee extensors and flexors at 60°/s, except for Peak TQ of the knee extensors, where no significant difference was found between TRT and SRT. Countermovement jump showed a decrease in eccentric time and an increase in concentric force in SRT group. SRT and TRT resulted effective to enhance the strength performance indices during the 8-weeks experimental protocol. Peak torque at 120°/s explained more of the contractile characteristic effects of SRT training than MVC, suggesting that slow-speed training can cause fast twitch fibers hypertrophy in elite athletes. Since slow-speed training is supposed to produce a decreased exercise-induced muscle damage, SRT method is a suitable option in strength training for futsal and team sports.